Personal values and trust of Europeans in national and EU institutions - Marjetica Primožič; Cene Bavec (Central European Public Administration Review, 2009)
The paper elaborates influence of the personal values of Europeans on their trust in national and EU institutions. We confirmed the hypothesis that personal values have no effect on this trust with an exception of citizens’ attitudes towards democracy and tolerance. In the countries where democracy is a strong personal value citizens also demonstrate high trust in national institutions, on the other side in the countries where solidarity is high valued they demonstrate high trust in EU institutions. Furthermore, we confirmed that there are statistically significant differences in trust in institutions between citizens of the old and the new EU27 member states, as well as differences in countries with different types of legal systems. In majority of the new EU members citizens have higher trust in EU institutions, but lower trust in national institutions than the EU average. On the other side, the old EU members demonstrate higher trust in national institutions and much divided trust in EU institutions. We also indicated that characteristics of the national legal system influence citizens’ trust in national institutions, but they have no influence on trust in EU institutions. Countries with the Scandinavian national legal system demonstrate very high trust in national institutions, meanwhile trust in national institutions in post-socialistic countries is nearly three times lower.